Modeling the seasonal and interannual variability (2001-2010) of chlorophyll-a in the Iberian margin - Reboreda, Rosa
A modeling study of the seasonal and interannual variability of chlorophyll-a has been carried out for the period 2001-2010 along the Iberian shelf and adjacent ocean. A high resolution regional configuration of the three-dimensional Regional Ocean Modeling System (ROMS) has been used, coupled to a N2PZD2-type biogeochemical model. Chlorophyll-a concentration ([Chl]) model outputs were compared to regional objective analysis of remotely sensed [Chl] data for the same period. The spatio-temporal variability of modeled and satellite derived [Chl] was analyzed applying an individual Empirical Orthogonal Function (EOF) analysis to monthly time series. Three main modes of sea surface [Chl] variability explained more than 90% of modeled variability and more than 85% of remotely sensed variability. The first EOF accounted for the spring phytoplankton bloom (March-April). The second EOF was related to the spring-summer coastal upwelling season (April-September). The third EOF showed a recurrent [Chl] minimum in winter coinciding with the maximum vertical mixing (February) for the northern part of the region. The influence of the hydrographic conditions on [Chl] variability was explored through a cross-correlation analysis of the three EOFs and an assortment of physical descriptors given by the model: namely the mixing/stratification cycles and the occurrence of coastal upwelling.